AB0002 Genetic study of three-prime repair exonuclease (TREX1) in the susceptibility to systemic lupus erythematosus (SLE) among egyptian patients. (15th June 2017) - Dessouki, D El; Abdel-Hamid, MS; Effat, L; Niazy, M; Kholoussi, N; Moneim, G Abdel; Abdel-Salam, GM
Abstract : Background: Interferon-alpha (IFNα) pathway has a crucial role in the pathogenesis of SLE. Many genes have been encoding with this pathway and their impaired expression have been reported in patients with SLE. TREX1 is a DNA exonuclease involved in the metabolism and clearance of single stranded DNA from apoptotic cells, which is impaired in SLE 1 . TREX1 mutations have been reported in SLE 2 . Objectives: Our study was aiming to assess the role of TREX1 in the genetic susceptibility to systemic lupus erythematosus (SLE) among Egyptian patients. Methods: Fifty SLE Egyptian patients and 50 age & sex matched healthy controls were included in this study. Based on the clinical history and immunological investigations, the 50 SLE patients were divided into two groups according to the presence of positive family history of autoimmune disease: Group I: 28 patients with positive family history & Group II: 22 patients with no family history. Further, the single exon of TREX1 and its flanking sequences were amplified by PCR and sequenced in both directions. Results: Our work showed a recurrent TREX1 polymorphism rs11797 (c.531C>T) among Egyptian patients (56%) in comparison to control group (36%) (p value of 0.070) especially in cases with NPSLE, seizures and chilblains; with minor allele frequency of 0.28 in cases and 0.18 in controls (p value=0.342). TREX1 polymorphism was present in 57.1% patients (16/28) of SLE patients in group I versus 54.5% patients (12/22) of SLE cases in, group II. The polymorphism was positively associated with neuropsychiatric manifestations (OR=7.000, 95% CI=0.791–61.975) and chilblains (OR=10.532, 95% CI=0.550–201.679). Furthermore, there was a statistically significant difference in cases with oral ulcers (p value=0.004), photosensitivity (p value=0.047) and seizures (p value=0.029). Conclusions: We confirm that rs11797 (c.531C>T) could be associated with the susceptibility to neurological manifestations among the studied SLE patients. References: Hur JW, Sung YK, Shin HD, Park BL, Cheong HS, and Bae SC (2008): TREX1 polymorphisms associated with autoantibodies in patients with systemic lupus erythematosus. Rheumatol Int; 28:783–789. Lee-Kirsch MA, Gong M, Chowdhury D, Senenko L, Engel K, Lee YA, et al. (2007): Mutations in the gene encoding the 3'-5' DNA exonuclease TREX1 are associated with systemic lupus erythematosus. Nat Genet; 39(9):1065–7. Disclosure of Interest: None declared